Evaluation of Folic Acid level in Serum of Smokers and Non Smokers Patients with Periodontal Disease: A Case-Control Study (Mustansiria Dental Journal, 2024)
Objectives: Periodontitis is a complex disease, the reason of which remained unclear. Folic acid belongs to B complex vitamins. It is vital for the formation and division of new cells, as it serves as a crucial cofactor in DNA synthesis. Without the presence of folic acid, epithelial cells fail to divide correctly. Folic acid levels can be influenced by a number of factors, one of which is cigarette smoking. This study aimed to measure serum concentration of folic acid among patients with periodontitis associated to their smoking behaviors. Materials and Methods: The study included 75 subjects; divided in the following groups: group-I: 25 Smokers with periodontitis, group-II: 25 Non-smokers with periodontitis and group-III: 25 Non-smoker with healthy periodontium (control group). Clinical parameters were recorded including: Plaque Index(PLI), Gingival Index GI, Bleeding On Probing (BOP), Probing Pocket Depth(PPD) and Clinical Attachment Loss(CAL). Blood samples were taken and evaluated in the laboratory for folic acid levels by enzyme-linked immunosorbent assay ELISA technique. Results: Significantly low concentration of folic acid encountered in serum of smokers with periodontitis as compared to healthy non-smoker controls (P < 0.001). Additionally, smokers with periodontitis showed significantly higher PLI, PPD and CAL means than non-smokers with periodontitisConclusion: The results of the present study indicate that folic acid levels were decreased significantly in smokers with periodontitis. Smoking has a negative impact on folic acid level and periodontal health.